The combination of paeonol, diosmetin-7-O-β-D-glucopyranoside, and 5-hydroxymethylfurfural from Trichosanthis pericarpium alleviates arachidonic acid-induced thrombosis in a zebrafish model - Lin, Shenghua; Ma, Honglin; Zhang, Shanshan; Fan, Wei; Shen, Chuanlin; Chen, Jiayu; Jin, Meng; Li, Kun; He, Qiuxia (Frontiers in Pharmacology, 2024)
Trichosanthis fruit (TF) is a classic medicinal material from Shandong, China. The peel of this fruit (Trichosanthis pericarpium, TP) is known to exert anti-thrombotic effects. However, the anti-thrombotic active components and mechanisms of TP have yet to be fully elucidated. Combined with zebrafish models and high performance liquid chromatography (HPLC), this study evaluated the endogenous anti-thrombotic effects with the combination of three compounds from TP. First, we used HPLC to investigate components in the water extract of TP. Next, we used the zebrafish model to investigate the anti-thrombotic activity of the three compound combinations by evaluating a range of indicators. Finally, the expression of related genes was detected by Real-timeQuantitativepolymerase chain reaction (qPCR).HPLC detected a total of eight components in TP water extract, with high levels of paeonol (Pae), diosmetin-7-O-β-D-glucopyranoside (diosmetin-7-O-glucoside), and 5-hydroxymethylfurfural (5-HMF). The most significant anti-thrombotic activity was detected when the Pae: diosmetin-7-O-glucoside:5-HMF ratio was 4:3:3. qPCR analysis revealed that the abnormal expression levels of f2, fga, fgb, vwf, ptgs1 and tbxas1 induced by AA were improved. The combination of Pae, diosmetin-7-O-glucoside and 5-HMF may alleviate AA-induced thrombosis by inhibiting the inflammatory reaction, coagulation cascade reaction and arachidonic acid metabolism pathways.